High‐Throughput Single‐Nanowire Optoelectronic Characterization Using Microfluidic Technology - Tharaka MDS Weeraddana; Keisuke Minehisa; Stephen A. Church; Charles Smith; Fumitaro Ishikawa; Patrick Parkinson (Advanced Photonics Research, 2025)
Technologies relying on single optoelectronic nanoparticles require characterization of individual particle performance, often demanding destructive dispersal of particles from solution. A microfluidic chip with an ultrathin channel (8 μm) provides a platform for the sequential high‐speed single‐particle characterization of functional nanomaterials using correlative spectroscopy and imaging. This platform is shown to allow study of semiconductor nanowires with measurement rates of up to 240 nanowires/minute in continuous operation, enabling a dramatically improved and statistically robust comparison of intrawire disorder with interwire homogeneity. An analysis of over 15 k GaAs/AlGaAs nanowires reveals that ensemble measurements overestimate the full‐width at half‐maximum of emission by more than 4× and statistical dispersion of electronic disorder by 28%, demonstrating the importance of single‐particle studies.